2021
DOI: 10.2217/fvl-2020-0395
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between Inherited Thrombophilia and Novel Coronavirus Pneumonia

Abstract: Aim: This study aimed to investigate the relationship between severe novel coronavirus pneumonia (NCP) and hypercoagulable conditions that predispose patients to thrombosis such as the prothrombin gene ( F2) rs1799963 (G20210A), factor V Leiden ( F5) rs6025 (G1691A) and PAI-1 (rs1799768). Patients: NCP-diagnosed 62 previously healthy patients were enrolled for the investigation of the thrombophilia-related polymorphisms. Materials & methods: The frequency of genotypes were compared with healthy control gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…[12][13][14] Few studies have been conducted on the relationship between COVID-19 and congenital coagulation disorders or the presence of polymorphisms that cause thrombophilia. 4,[14][15][16][17] In the present study, the relationship between the severity of the COVID-19 clinical picture and some polymorphisms that cause thrombophilia were investigated. Factor V, one of the coagulation factors, has one of the most important roles in coagulation factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12][13][14] Few studies have been conducted on the relationship between COVID-19 and congenital coagulation disorders or the presence of polymorphisms that cause thrombophilia. 4,[14][15][16][17] In the present study, the relationship between the severity of the COVID-19 clinical picture and some polymorphisms that cause thrombophilia were investigated. Factor V, one of the coagulation factors, has one of the most important roles in coagulation factors.…”
Section: Discussionmentioning
confidence: 99%
“…DIC has been associated with abnormal coagulation, thrombus, and poor prognosis. 1,3 Studies on factors that cause different clinical pictures among infected patients are very limited 4 . Microvascular embolisms and coagulation disorders worsen the clinical picture, especially in patients who need intensive care, and death is observed more frequently in patients who develop coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies concerning the association of thrombophilic mutations and novel coronavirus virus pneumonia showed conflicting results. Kiraz et al (2021) reported no statistically significant difference in the frequency of these polymorphisms in patients with severe COVID-19 pneumonia and the healthy population ( 32 ). Conversely, Conversely, Appenzeller et al presented a case of a previously healthy 21-year-old male with extensive thromboembolism in the absence of obvious thrombophilic risk factors; the thrombophilia screening revealed the presence of the heterozygous factor V Leiden mutation, and despite the absence of clinical presentations of COVID-19, he tested positive ( 33 ).…”
Section: Mechanism Of Thrombosis In Covid-19 Patientsmentioning
confidence: 99%